1996
DOI: 10.1073/pnas.93.19.10428
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of an attenuated virus by design: engineering a novel receptor for a noninfectious foot-and-mouth disease virus.

Abstract: To gain entry into cells, viruses utilize a variety of different cell-surface molecules. Foot-and-mouth disease virus (FMDV) the epitope recognized by the mAb and also regained the ability to be neutralized by the mAb. Moreover, RGD-deleted virions that are noninfectious in animals and other cell types grew to high titers and were able to form plaques on scAb/ ICAMI cells. These studies demonstrate the first production of a totally synthetic cell-surface receptor for a virus. This novel approach will be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Using CLPs as a model system for cell binding, VP7 mutants were assessed for their cell attachment capability and the data obtained demonstrated clearly that mutated CLPs either did not bind to Culicoides-derived cells at all or bound at much reduced level compared to the wt CLPs, suggesting a role for RGD in core uptake by the insect cells. MAbs specific for integrins that recognize the RGD sequences of viral proteins block virus attachment and infectivity of other viruses (33,52,61,62). In our study we have used the VP7 MAbs that are RGD site specific (e.g., H1.5 and CLPIII) to block the CLP attachment and have demonstrated that such MAbs interfere with CLP binding to KC cells.…”
Section: Vol 75 2001mentioning
confidence: 89%
“…Using CLPs as a model system for cell binding, VP7 mutants were assessed for their cell attachment capability and the data obtained demonstrated clearly that mutated CLPs either did not bind to Culicoides-derived cells at all or bound at much reduced level compared to the wt CLPs, suggesting a role for RGD in core uptake by the insect cells. MAbs specific for integrins that recognize the RGD sequences of viral proteins block virus attachment and infectivity of other viruses (33,52,61,62). In our study we have used the VP7 MAbs that are RGD site specific (e.g., H1.5 and CLPIII) to block the CLP attachment and have demonstrated that such MAbs interfere with CLP binding to KC cells.…”
Section: Vol 75 2001mentioning
confidence: 89%
“…Adeno-associated virus type 2 can use a variety of carbohydrate or glycoprotein receptors or capsid-receptor cross-linking systems to mediate cell transduction (5,22,61,70,89,90). Foot and mouth disease virus can infect through an antiviral scFv fused to intracellular adhesion molecule 1 (62). In contrast, poliovirus requires the poliovirus receptor for infection, and binding to the N-terminal domain of the receptor leads to the changes in the capsid structure required for infection, including the loss of the VP4 protein and exposure of hydrophobic portions of VP1 (80).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction with integrin receptor molecules is not required for FMDV uncoating, and the virus can infect cells by an antibody-dependent pathway [153,154,184]. This suggests that expression at the cell surface of particular molecules, which can act as receptors or coreceptors for the virus, may exert an important selective pressure on FMDV.…”
Section: Rgd-independent Mechanisms Of Cell Recognitionmentioning
confidence: 99%